2009
DOI: 10.3831/kpi.2009.12.1.043
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Ginger Herbal Pharmacopuncture for Practical Application

Abstract: Objective : The purpose of this study is to present the standard for practical application of ginger herbal pharmacopuncture Material and Methods : We refer to ancient literatures and the recent papers for ginger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Bee venom is effective in treating pain and has recently been applied to various diseases such as arthritis, adhesive capsulitis, lupus, and cancer [1][2][3]. Bee venom acupuncture (BVA), one of the most frequently used techniques recently, involves intradermally or intramuscularly administering a small amount of refined bee venom into specific acupoints or painful areas [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bee venom is effective in treating pain and has recently been applied to various diseases such as arthritis, adhesive capsulitis, lupus, and cancer [1][2][3]. Bee venom acupuncture (BVA), one of the most frequently used techniques recently, involves intradermally or intramuscularly administering a small amount of refined bee venom into specific acupoints or painful areas [4].…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Bee venom acupuncture is a pharmacopuncture that takes advantage of diluted bee venom instead of distilled herbal decoctions. [15,16] Although pharmacopuncture has used for treating various diseases, it is most often applied in musculoskeletal disorders, and many studies on its therapeutic efficacy have been reported. [13,14] The treatment of nerve entrapment syndrome with pharmacopuncture alone or combined with KM intervention has been reported, and clinical Medicine evidence suggests that pharmacopuncture treatment can reduce pain by relieving the entrapment of the peripheral nerves that dominate the area, thus improving the ischemic state of the nerve stem.…”
Section: Introductionmentioning
confidence: 99%
“…Bee venom (BV) is an animal toxin that contains several active compounds, such as enzymes, peptides, non-peptide components, and biologically active amines. BV demonstrates the potential to be used as a beneficial pain treatment [ 10 , 11 ]. There are several types of BV therapies available, such as bee sting therapy, bee venom acupuncture (BVA), and the external use of BV products.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, this treatment modality also exhibits a high risk of developing adverse side effects [ 12 ]. On the other hand, BVA, which involves the administration of BV diluted with saline into a specific acupoint, has been used to treat different types of pain in the clinical fields of traditional, complementary, and alternative medicine [ 10 ] and does not exhibit the same adverse risks as those observed with bee sting therapy.…”
Section: Introductionmentioning
confidence: 99%